Een Verzameling Realisme Renaissance. - Hemelrijk, Liesbeth; Middendorp, Jan (Rotterdam : Caldic Collectie, 1991)
Akkerman, Philip ; Banks, Nick ; de Blieck, Marc ; Emmerik, Pam ; Felius, Marleen ; Hynckes, Raoul ; Janssen, Edwin ; Jongenelis, Hewald ; Koch, Pyke ; Korsmit, George ; Mantje, Aldert ; Mistiaen, Carlo ; Noordermeer, Jaap ; Scholte, Rob ; Stepanek, Alice ; Maslin, Steven ; Stuurman, Frans ; Tempi & Wolf ; de Vries, Jaap ; Wertheim, C.A. ; Willink, Carel ; Worst, Jan
Een Verzameling Realisme Renaissance, Caldic Collectie, Rotterdam, 1991
boek